2023
DOI: 10.1109/access.2023.3271720
|View full text |Cite
|
Sign up to set email alerts
|

Unlocking Signal Processing With Image Detection: A Frequency Hopping Detection Scheme for Complex EMI Environments Using STFT and CenterNet

Abstract: Accurate detection and parameter estimation of frequency hopping (FH) signals remain challenging in FH signal-based transmission systems. This study proposes a scheme combining time-frequency analysis (TFA) and deep learning (DL)-based image processing algorithms to alleviate the degradation of detection accuracy and estimation performance caused by complex electromagnetic interference (EMI). A short-time Fourier transform (STFT) was used to obtain the signal spectrogram, which reflects the signal energy in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…• Partial areas of wideband signal may be detected as the narrowband signals at a small scale because of the fluctuation within signal bandwidth. An example is shown in Figure 6, three narrowband signals are falsely detected within the wideband signal at scale 2 6 ;…”
Section: Merging and Selective Elimination Of The Signal Detection Re...mentioning
confidence: 99%
See 2 more Smart Citations
“…• Partial areas of wideband signal may be detected as the narrowband signals at a small scale because of the fluctuation within signal bandwidth. An example is shown in Figure 6, three narrowband signals are falsely detected within the wideband signal at scale 2 6 ;…”
Section: Merging and Selective Elimination Of The Signal Detection Re...mentioning
confidence: 99%
“…Through the estimation and clustering of the noise top of the modified spectrum, the adaptive energy detection threshold estimation value is obtained. The wavelet transform of the wideband spectrum at scale 2 6 and 2 10 are shown in Figure 11. It can be found that the extreme values of the wavelet transform corresponding to the edge of the narrowband signal are obvious at small-scale transform, while the extreme values of the wavelet transform corresponding to the edges of the wideband signal are obvious at the large-scale transform.…”
Section: (1) Simulation Analyses Of the Feasibility Of The Algorithm ...mentioning
confidence: 99%
See 1 more Smart Citation
“…From the aspect of signal analysis, the transform-based methods, including short-time Fourier transform (STFT)-based [3][4][5][6], wavelet transform-based [7][8][9][10], and autocorrelation analysis-based [11] methods, are the most straightforward approaches for signal parameter estimations. Even in recent years, transform-based methods have continued to be extensively developed.…”
Section: Introductionmentioning
confidence: 99%